Toward food sovereignty and self-sufficiency in Latin America and the Caribbean: opportunities for agricultural complementarity Hacia una soberanía y autosuficiencia alimentaria en América Latina y el Caribe: oportunidades de complementariedad agrícola - Cango, Pedro (2022)
Food self-sufficiency is a relevant political issue in many countries, developed and developing, particularly to satisfy the internal nutritional needs of the population and face situations in which the prices of basic products are unstable or when a country faces an external shock. Improving resilience involves strengthening local rural communities to meet demand with domestic production. The member countries of Latin America and the Caribbean (LCN) produce enough food to sustain their population and to be one of the world’s largest food exporters. From the theoretical discussion and using data from FAO, the research shows that there is a potential to improve food sovereignty and to define food and agricultural policies through agricultural complementarity among the LCN countries. Diverting part of the current trade with third parties to intraregional trade, for products in which the region has a comparative advantage, would mean that LCN countries could save up to 2.7 billion dollars per year, that is, 6.8% of total imports of food in 2018, avoiding the outflow of foreign currency and promoting greater economic integration between countries.